Epidemiological, Clinical, and Diagnostic Aspects of Urinary Tract Infection in Newborns at the Departmental Teaching Hospital of Borgou-Alibori (DTH-B/A) in Benin (Journal of Renal and Hepatic Disorders, 2022)
To study epidemiological and diagnostic aspects of urinary tract infection (UTI) in newborns at the Departmental Teaching Hospital of Borgou-Alibori (DTH-B/A). This was a cross-sectional study conducted from April 1, 2019 to September 30, 2019 and concerned all newborns admitted to the neonatal unit of DTH-B/A. According to the National Agency for Health Accreditation and Evaluation (NAHAE)recommendations of 2002, all symptomatic newborns who did not have a visible malformation outside the genitourinary system and whose parents gave their consent were included in the study. The census was exhaustive despite the calculated minimum size of 109 newborns. Urine sedimentation and cytobacteriological examination of urine samples, taken in adhesive bags after local disinfection, demonstrated presence of pathogenic microbes. Sensitivity of detected microbes was studied to different antibiotics. Interpretive reading of antibiograms was established according to the Standards of the French Society of Microbiology (FEMS), edition 2012. If UTI was confirmed, an abdominopelvic ultrasound was performed in search for a malformative uropathy as a contributing factor in newborns. A standardized survey was developed for data collection. The data entered were analyzed using the Epi info software, version 3.5.4. In all, 124 newborns were included in the study. UTI accounted for 8.06% of all neonatal infections and 2.15% of admissions. The average age of onset was 7.8 days, with a gender ratio of 1:1. The main clinical manifestations were jaundice and respiratory distress. Microbes involved were Staphylococcus aureus (6/10), Escherichia coli (2/10), and Klebsiella oxytoca (2/10). The resistance of microbes to antibiotics was generally high. No abnormalities were revealed in the ultrasound. Although neonatal UTI is not a rare infection, bacterial resistance is of concern.
Keywords: Benin; newborn; urinary tract infection